Identifying modifiable factors associated with health optimism in older adults - Rai, R.; Jongenelis, Michelle; Pettigrew, S.; Jackson, B.; Newton, R. (Routledge, 2017)
Objective: Despite the documented importance of health optimism for enhancing health outcomes, very little work has been done to examine who experiences health optimism and under what conditions. The present study sought to identify modifiable factors associated with health optimism that could constitute the focus of future intervention efforts designed to promote health optimism among older people. Design: Participants were 453 (44% males) community-based Western Australians aged 60+ years (M = 70.39 years, SD = 6.06). Participants completed questionnaires to assess sociodemographic characteristics and provided information relating to physical and psychological health status. Results: Almost a quarter of participants (24%; n = 108) were classified as health optimists. Results from a multivariate regression analysis found quality of life, psychological well-being, and age to be directly and positively associated with health optimism. A subsequent path analytic model found depression (negatively) and self-efficacy (positively) to be indirectly associated with health optimism via both psychological well-being and quality of life. Conclusion: These findings extend the limited evidence on health optimism in older adults by identifying various modifiable factors that may constitute potential areas of focus for future interventions designed to enhance health outcomes via the fostering of health optimism.